Avoidance of energy hole problem based on feedback mechanism for heterogeneous sensor networks - Tang Liu; Jian Peng; Jin Yang; Guo Chen; Wenzheng Xu (International Journal of Distributed Sensor Networks)
The application-based wireless sensor networks have the energy hole problem when considered for performance measures in balancing the energy load. To avoid the energy hole problem for heterogeneous sensor networks, a feedback mechanism–based unequal clustering algorithm is proposed. In the initial stage of the network, this article divides the network into several layers with different layer heights by only considering the distance from nodes to the sink. Then, this article introduces a feedback mechanism and dynamically changes the size of each cluster according to the feedback value calculated by the sink. After the size of each cluster varies for several rounds, the energy consumption between each cluster will tend to be balanced. To save the energy consumption cost of receiving the sink feedback signal, this article proposes the termination condition for the feedback process. When the termination condition is satisfied, the feedback process finishes and the network turns into the stable clustering stage. The simulation results show that compared with the existing algorithms of data transmission, feedback mechanism–based unequal clustering algorithm can make better use of node energy and prolong the network lifetime.